Treatment of intraarticular displaced fractures of the calcaneus bone using nail blocked calcanail - Weiss, Marcin; Dolata, Tomasz; Weiss, Waldemar; Maksymiak, Martyna; Kałużny, Krystian; Kałużna, Anna; Żukow, Walery; Hagner-Derengowska, Magdalena (Journal of Education, Health and Sport, 2018)
The aim of this new technic in our hospital is to describe this method of treatment for displaced articular fractures of the calcaneus, which offered the following advantages: (a) the creation of a working channel that provides also a significant bone autograft, (b) the intrafocal reduction of the displaced articular surface, (c) the insertion of a locking nail that maintains the reduced articular surface at the right height, (d) the possibility to switch from an ORIF to a reconstruction arthrodesis with the same approach and instrumentation in case of severely damaged posterior facet.